Experimental Investigations to Study Cutting Temperature and Forces During Cortical Bone Drilling - Jindal, Rohit (My University, 2016)
Drilling through bone is necessary action during the orthopaedic surgery. The drilling through the bones is majorly same as the mechanical drilling but it need more expertise and skills because it involved human as part of work. The mechanical drilling during orthopaedic surgery may harm the subject bone and bring to the surgeon for cure. For better treatment the surgeon must do the drilling in a manner that it should not damage the surroundings. To keep these points in consideration this research work has been carried out. The main drilling parameters i.e. rotational speed, feed rate and type of drill are under observation at different levels. This research work focuses to optimize the involving parameters for the less thermal necrosis, less surface damage and less thrust force exerted between tool and work material. Using L 16 taguchi mixed orthogonal array the optimized set of parameters has been suggest for all the response. Scanning electrode microscopy (SEM) images of the bone drilled samples helps to get the level of surface damage and the supports the results of surface roughness. An analytical model has been purposed for raise in temperature for all the experiments performed. The experimental and analytical results are in better agreement.
Keywords: Bone Drilling, Thermal Necrosis, SEM